Implementation of actuated and flow-measuring gates on the Greeley No. 2 canal in northeastern Colorado - Magnuson, Donald O., author; Smith, Stephen W., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
New Cache La Poudre Irrigating Company (http://www.newcache.com/) began the first phases of modernizing the 114-year-old canal in recent years. The Company has built new equalizer reservoirs, a 30 CFS pump station, and a new 3,000 acre foot storage reservoir using concessionary loans available from the Colorado Water Conservation Board. Further, the outlet works out of the Company's long-time equalizer reservoir on the Greeley #2 Canal has been replaced and modernized. As an integral part of the overall canal modernization, various approaches to actuating gates, measuring flows, and initiating SCADA were evaluated. The Company studied and toured SCADA installations in four states of the United States and in two states of Australia. Ultimately, the Rubicon actuated and flow measuring gates were selected and eight gates have been installed on the canal in the past two years. Portions of the Greeley #2 Canal, the river diversion on the Cache La Poudre River, and the discharges from two reservoirs can now be monitored and controlled from the Company's office in Lucerne, Colorado. The process of evaluating SCADA and actuated gates will be described as well as current operations. Further expansion of the system is anticipated in the future that will likely lead the Company toward full canal automation. The current short term strategy for future expansion of the system will be described.
SCADA and related technologies
Actuated and flow-measuring gates
Not digitized by CSUL Digital Services.
Presented at SCADA and related technologies for irrigation district modernization, II: a USCID water management conference held on June 6-9, 2007 in Denver, Colorado.